Flow and erosion at a bend in the braided Jamuna River - UDDIN, Mohammad Nazim; RAHMAN, Md. Munsur (International journal of sediment research, 2012)
The braided Jamuna River frequently changes its courses. Sometimes the secondary channel in a braided river acts as a single thread meandering channel. In the present study an attempt has been made to investigate the flow patterns and to estimate the rate of bank erosion in a bend along the Jamuna River. The three dimensional （3D） flow velocities were measured using Acoustic Doppler Current Profiler （ADCP）. It is found that the near bank velocity is amplified by 1.1 to 1.3 times as compared with the section averaged velocity. A dominant secondary current is found in the upstream bend. The evolution as well as decay of the secondary current is not as clear as it is found in the laboratory experiments. It is revealed from the analysis of the flow process that the causes of higher rate of erosion at the study bend are the oblique flow near bankline, six times amplified shear velocity than critical shear velocity near bankline and the secondary current which acts as a sediment transporting agent from the outer bank towards the inner bank or the sand bar. Based on the flow processes, a simplified erosion prediction model is developed and applied to estimate the rate of erosion at a selected bend. Finally the predicted results have been compared with the observed data at the bend and all the available data at other bends along the Jamuna River.